2017
DOI: 10.1098/rsta.2015.0434
|View full text |Cite
|
Sign up to set email alerts
|

Origins and demonstrations of electrons with orbital angular momentum

Abstract: One contribution of 14 to a theme issue 'Optical orbital angular momentum' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 74 publications
(136 reference statements)
0
32
0
Order By: Relevance
“…At the time of writing of this review, the best transmission e ciency reported by Grillo et al is 37% out of a theoretical limit of 38% for their partially blazed phase mask. On the other hand, McMorran's group (McMorran et al, 2017) reported a much larger value of 70% for the absolute transmission e ciency for their blazed mask. Clearly more work is needed to investigate the practical limits to the generation e ciencies using optimized blazed phase masks.…”
Section: Blazed Phase Maskmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of writing of this review, the best transmission e ciency reported by Grillo et al is 37% out of a theoretical limit of 38% for their partially blazed phase mask. On the other hand, McMorran's group (McMorran et al, 2017) reported a much larger value of 70% for the absolute transmission e ciency for their blazed mask. Clearly more work is needed to investigate the practical limits to the generation e ciencies using optimized blazed phase masks.…”
Section: Blazed Phase Maskmentioning
confidence: 99%
“…For practical reasons, the holographic di↵raction mask and the aperture masking methods are di cult to implement for atomic size vortex beams, making the astigmatism transformation method currently the most realistic method for atomic scale pure vortex beams. For e cient sorting of electron vortex beams in general, electron optical are preferred and a refractive device has recently been proposed by McMorran et al (2017).…”
Section: B Mode Conversion Analysismentioning
confidence: 99%
“…The study of orbital angular momentum has had an impact beyond the field of optics and an issue devoted to OAM would not be complete without papers looking beyond optics. We have two discussing the existence of electron vortices and their angular momentum properties [57,58].…”
Section: Recent Developments and This Theme Issuementioning
confidence: 99%
“…For example, diffraction holograms can be used in a scanning transmission electron microscope to remove aberrations [1], implement new types of interferometric phase contrast [2,3], and produce electron probes with phase vortices and quantized angular momentum [4,5].We are currently investigating the use of nanoscale gratings for off-axis STEM interferometry ( Figure 1). We have used a single grating in a scanning transmission electron microscope (STEM) to form a pathseparated electron interferometer [6].…”
mentioning
confidence: 99%
“…For example, diffraction holograms can be used in a scanning transmission electron microscope to remove aberrations [1], implement new types of interferometric phase contrast [2,3], and produce electron probes with phase vortices and quantized angular momentum [4,5].…”
mentioning
confidence: 99%